Pengaruh Narsisme Klien Dan Pola Pikir Auditor Terhadap Penilaian Risiko Kecurangan - Prawina, Annisa Cikal; Uzliawati, Lia; Sabaruddinsah, Sabaruddinsah (Politeknik Ganesha Medan, 2024)
Financial statements are an important element in business because they reflect the state of a company. With the information in it, it can help internal and external parties consider long-term decisions. Therefore, reasonable financial reports are needed, namely based on Financial Accounting Standards and free from fraud so as not to trigger financial and non-financial losses. Fraud risk assessment is the basis for detecting fraud. With risk assessment, the auditor can determine the nature and level of audit procedures designed, and can be more sensitive to fraud signals from red flags that occur. This study aims to prove the relationship between client narcissism and auditor mindset towards fraud risk assessment based on attribution theory. In this study, auditors who work at the Jakarta Regional Public Accounting Firm with a minimum position as a junior auditor and at least one year of experience as an auditor are used as research samples. The number of samples used was 73 auditors. The data source of this research is primary data. The data collection technique with the method of distributing questionnaires with multiple linear regression analysis method. The results show that: client narcissism has no effect on the fraud risk assessment, and the auditor's mindset has a significant effect on the fraud risk assessment.